UPAYA MENINGKATKAN KEMAMPUAN BERDISKUSI DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE PAIR CHECK PADA MATERI SUHU DAN KALOR KELAS X6 SMA NEGERI 8 KOTA JAMBI - Dewi, Difa Jefri Oktifia; Hidayat, M; Pathoni, Haerul (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2019)
This research aims to determine the implementation of model of cooperative learning type pair check to improve the ability to discuss and learning outcome in X6 class of State High School 8 Jambi City. This research was a classroom actions research carried out by three cycles. Each cycle through the planning stages of action, implementation of action, observation, evaluation, analysis and reflection. The results showed that there was an increase in discussions and student learning outcomes. The ability of student discussions on the I cycle has quite a category of increase in the III cycle into good categories. The average result 74.80 (cycle I) has increased to 78,67 (cycle III). Based on the results of this study can be concluded that with the implementation of the model of cooperative type pair check can improve the ability to discuss and learning outcome in the X6 class of State High School 8 Jambi City on the subject of temperature and heat.